Menuju Desentralisasi Pengelolaan Administrasi Pendidikan - M. Dimyati Safari (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2001)
Toward Desentralization in Managing Educational Administration. The implementation of Undang-Undang No. 22/1999 on Regional Government, or called Regional Autonomy, and Undang-Undang No. 25/1999 on Finance Balance between the Central and Regional Government has a large number of implications, including to needs for decentralization of educational administration. Some aspects need to be taken into account in implementing decentralization of educational administration: national intentions, social justices, regional needs, implementation efficiencies, and reform capacities.